"Bueno, hasta luego": El uso de ’bueno’ en conversaciones - Carmen Gregori Signes (Miscelánea: A Journal of English and American Studies, 1996)
This paper presents a possible approach to the analysis and use of the Spanish discourse marker bueno in everyday conversation. The analysis is part (and at the same time a result) of a project in which the functions of bueno are compared to those of well in English conversations. In this project English and Spanish discourse markers are being compared in order to find similarities and differences between their function and use in conversation. In this paper we do not try to reach definitive conclusions since the corpus needs to be extended and it is necessary to elaborate a framework in order to classify every occurrence of the different markers in a systematic way.